2010
DOI: 10.1007/s10144-010-0239-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of serotiny and rainfall‐cued dispersal on fitness: bet‐hedging in the threatened cactus Mammillaria pectinifera

Abstract: Serotiny-the retention of seeds in the mother plant for over a year-in unpredictable environments may increase the probability that at least some seeds are dispersed during favorable periods. Propagules may be expelled when environmental cues announcing favorable conditions occur, or be gradually released into the environment. This could be a bet-hedging strategy increasing the long-term fitness by reducing interannual variability in reproduction. However, the impact of seed retention on the population dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 37 publications
1
16
0
4
Order By: Relevance
“…These discontinuous outbreaks may allow the population size to recover or even increase between insect surges. As in our study, Peters et al (2011) found evidence for predation only in some years, with very low adult mortality in the remaining period. In May 2011, we surveyed both sites, and found that mortality at NDS remained low (annual average 0.9%) and had diminished in DS since 2009 (7.7%), confirming that the low survival observed during years 3 and 4 was a transitory event.…”
Section: Vital Rates and Population Dynamicssupporting
confidence: 42%
See 2 more Smart Citations
“…These discontinuous outbreaks may allow the population size to recover or even increase between insect surges. As in our study, Peters et al (2011) found evidence for predation only in some years, with very low adult mortality in the remaining period. In May 2011, we surveyed both sites, and found that mortality at NDS remained low (annual average 0.9%) and had diminished in DS since 2009 (7.7%), confirming that the low survival observed during years 3 and 4 was a transitory event.…”
Section: Vital Rates and Population Dynamicssupporting
confidence: 42%
“…In the cactus Mammillaria pectinifera, a cerambicid outbreak was observed to cause a stronger reduction in k in a disturbed site (Valverde and Zavala-Hurtado 2006) compared to a relatively preserved one (Peters et al 2011). Insect outbreaks may be more probable on plants exposed to pulsed water stress (Huberty and Denno 2004), which seems to be amplified by CAD.…”
Section: Vital Rates and Population Dynamicsmentioning
confidence: 97%
See 1 more Smart Citation
“…hutzilopochtli, Flores-Martínez et al, 2010;M. gaumeri, Ferrer et al, 2011;Peters et al, 2011;M. mystax, Saldivar y Navarro, 2012), es un gé-nero poco estudiado dada su riqueza y amplitud de hábitats en los que se encuentra en México y EUA.…”
Section: Marisol Martínez-ramosunclassified
“…El ciclo de vida fue dividido por el diámetro de los individuos en cinco categorías de tamaño (0.01 > a < 1 cm Plántula, 1 ≤ a < 2 cm Juvenil, 2 ≤ a < 3 cm Adulto 1, 3 ≤ a < 4 cm Adulto 2 y ≥ 4cm Adulto 3) y una categoría de semilla a la que se le asignó una probabilidad pequeña (0.0005) al desconocer la probabilidad real de permanencia en el banco de semillas. Los experimentos de germinación (ver apartado de germinación) mostraron que las semillas > 1 año siguen germinando lo que sugiere al menos la posibilidad de un banco de semillas semi-permanente de corta duración para Mammilaria humboldtii, además de que se han reportado bancos de semillas para otras especies del género Mammillaria (Bowers, 2005;Valverde y Zavala-Hurtado, 2006;Peters et al, 2011). El crecimiento y supervivencia se registraron en el mes de mayo de 2012 y 2013 después de la época reproductiva.…”
Section: Materiales Y Métodosunclassified